STUDIES ON THE EFFECT OF SUCROSE, LIGHT AND HORMONES ON MICROPROPAGATION AND IN VITRO FLOWERING OF WITHANIA SOMNIFERA VAR. JAWAHAR-20 - S. Nathiya; D. Pradeepa; T. Devasena; K. Senthil (Journal of Animal and Plant Sciences, 2013)
Withania somnifera (solanaceae) popularly, known as “Ashwagandha” is one of the major herbal components of geriatric tonics mentioned in Indian system of medicine. In the present study, effect of various factors on in vitro germination such as sucrose concentration (1%, 2% and 3%) and light intensity (light and dark) in half strength Murashige Skoog medium (1/2 MS) has been studied. 1/2 MS supplemented with 2% sucrose incubated in dark at 25˚C was found to give maximum rate of germination compared to ½ MS supplemented with 1% and 3% sucrose. Different hormonal concentrations were used to test the efficiency of micro shoot formation at different time intervals after inoculation for a period of 90 days with regular subculturing. The maximum number of microshoots was developed in MS media supplemented with 0.5 BAP and 0.05 TDZ followed by 1.0 BAP and 0.05 TDZ. The well-propagated shoots were transferred to elongation media. MS medium supplemented with 1.0 KN and 0.05 BAP showed maximum elongation of shoots. The multiple shoots obtained from 0.5 BAP and 0.05 TDZ; 1 BAP and 0.05 TDZ were transferred to flower induction medium. Different hormonal combination were used to induce flowering, MS medium supplemented with combination of 1 KN and 0.05 BAP exhibits 66% of flowering followed by 0.1 BAP. The matured and immatured pollens in the flowers were observed by pollen staining which contribute to the mode of transfer of genes from one generation to another. Thus the number of matured pollens were more in the in vitro flowers similar to in vivo flowers. In this study an effective methodology for the in vitro seed germination, propagation and flowering was standardized.
Keywords: in vitro flowering; micropropagation; pollen staining; Withania somnifera